PENGARUH TEKNOLOGI INFORMASI DAN SISTEM INFORMASI TERHADAP KINERJA PELAYANAN PUBLIK PADA PEGAWAI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN BOYOLALI - Tika Dayanti Nilasari; Suharno Suharno; Bambang Widarno (Universitas Slamet Riyadi, 2020)
The purpose of this research was to analyze the influence of information technology and information systems as well as analyze the dominant influence between information technology and information systems on performance of service public Service Employees on the population and Notes Civil Boyolali Regency.This type of research survey, with data-collecting interviews, questionnaires, and study of the literature.Test instrument validity and reliability. Data analysis techniques using multiple linear regression, t-test, F-test and test the coefficient of determination.The results showed there are significant effects of information technology on performance of public service in the Department of population and civil registration Boyolali Regency.There are significant effects of information systems on performance of public service Employees in the Department of population and civil registration Boyolali Regency.